Большая энциклопедия России. Самое полное современное издание (Эксмо, 2008)
Экземпляры: Колесурская библиотека (20101109) / Инвентарный номер: 197282 / Цена: 511.50 / Авт.знак: Б 79 / ГРНТИ: 00 / ББК: 92(2)